2021
DOI: 10.3390/geosciences11070295
|View full text |Cite
|
Sign up to set email alerts
|

Lithological and Geochemical Heterogeneity of the Organo-Mineral Matrix in Carbonate-Rich Shales

Abstract: The paper discusses the issues of interaction of the organic matter and the siliceous-carbonate mineral matrix in unconventional reservoirs of the Upper Devonian Domanik Formation of the Upper Kama Depression of the Volga-Ural Basin. The Domanik Formation is composed of organic-rich low-permeability rocks. Lithological and geochemical peculiarities of rocks were studied using light microscopy, X-ray diffraction analysis (XRD), scanning electronic microscopy (SEM), and evaporation method. Organic matter was exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…According to pyrolytic studies, the DF refers to mature oil-producing rocks [38]. The DF shales are characterized by extremely low permeability and porosity (0.66 to 1.87), fractures and cavities in carbonate mineral matrix, inter-and intraparticle pores predominantly in the carbonate mineral matrix, and pores in the organo-mineral part of the rock [10,39,40]. The Domanik Formation is often considered as an analogue of the Eagle Ford Formation [32,41].…”
Section: Methodsmentioning
confidence: 99%
“…According to pyrolytic studies, the DF refers to mature oil-producing rocks [38]. The DF shales are characterized by extremely low permeability and porosity (0.66 to 1.87), fractures and cavities in carbonate mineral matrix, inter-and intraparticle pores predominantly in the carbonate mineral matrix, and pores in the organo-mineral part of the rock [10,39,40]. The Domanik Formation is often considered as an analogue of the Eagle Ford Formation [32,41].…”
Section: Methodsmentioning
confidence: 99%
“…Different authors have shown how geochemical trends allow scientists to improve the productivity evaluation of the formation [9]. Integrated lithological and geochemical studies allow scientists to identifying intervals, where organic matter can form in association with the siliceous-carbonate matrix [10,11] Rock-Eval methods are usually used as quick, inexpensive, and reliable screening options for source rock/reservoir rock characterization. There could only be occasionally available geochemical results due to the limitations and utility.…”
Section: Introductionmentioning
confidence: 99%
“…Much attention is paid to the study of the kerogen chemical structure [7], variation of kerogen type on the depth [8], the interaction of the organic matter and mineral matrix [9], void space [10], and the kerogen-related multiscale heterogeneity and anisotropy [11] of the Bazhenov formation sediments.…”
mentioning
confidence: 99%
“…Bogdanovich et al [9] discuss the issues of interaction of the organic matter and the siliceous-carbonate mineral matrix in organic-rich low-permeability rocks of the Upper Devonian Domanik Formation (Upper Kama Depression, Volga-Ural Basin, Russia). The authors identify intervals where organic matter can form a complex association with the siliceous-carbonate matrix using results of a complex study with light microscopy, X-ray diffraction analysis, scanning electronic microscopy, evaporation method, and the Rock-Eval pyrolysis.…”
mentioning
confidence: 99%